Design of Comprehensive Monitoring on Hybrid Photovoltaic and Thermoelectric Generator Using IoT - Rahman, Yuli Asmi; Adam, Andi Arham; Samnur, Samnur; Basri, Basri; Anwar, Khairil; Hatib, Rustan; Mustofa, Mustofa (Journal of Applied Engineering and Technological Science (JAETS), 2024)
The study aims to design and develop a more efficient measurement monitoring system based on influential parameters for the performance of hybrid PV and TEG modules using IoT with the Thingspeak application. The parameters measured include the PV top and bottom surface temperatures and output current and voltage, the surface temperatures of the TEG's hot and cold sides, their respective current and voltage outputs, air humidity, and solar intensity. This IoT-based monitoring system experimental method utilizes two types of PV, polycrystalline and monocrystalline, each rated at 50 Wp, in a hybrid configuration with 5 TEG modules attached to the back of the solar panel. The monitoring design results indicate that sensor measurements were accurate and data readings were reliable. The temperature difference between the two sides of the TEG was measured up to 21.7°C, and the hybrid efficiency of the monocrystalline PV with TEG showed better results compared to the polycrystalline setup, achieving optimum efficiency above 6%, with the PV surface temperature maintained at an average of 50°C. Additionally, IoT monitoring revealed the effect of air humidity on TEG performance: lower air humidity resulted in a larger ?T, peaking at 21.7°C with humidity at 39.1%. Therefore, this study recommends using IoT technology for observational data collection on system performance, particularly for PV and TEG, with sensor component modifications tailored to the characteristics of the targeted sensor object.